Crazy blood : [large type] a novel - Parker, T. Jefferson (Thorndike Press large print core series., 2016)
Two half-brothers from a powerful skiing dynasty whose births were marked by violence and betrayal play out their fierce rivalry on one of the world's most perilous ski slopes while the women in their lives scheme to destroy and protect them. By the best-selling author of Storm Runners. --Publisher